Death zone! : can humans survive at 26,000 feet? - Piper, Ross. (Mankato, Minn. : Capstone Press, 2008)
Presents the science behind mountain climbing, including the effects of high altitudes on the human body.
Includes bibliographical references (p. 31) and index.
5.3
3-6
Keywords: Altitude, Influence of -- Juvenile literature; Mountaineering -- Physiological aspects -- Juvenile literature; Altitude, Influence of; Mountaineering -- Physiological aspects; Environmental influence on humans; Mountaineering -- Physiological aspects